Challenges and opportunities of local engagement in coral restoration at Laughing Bird Caye National Park - Uribe-Castañeda, Natalia (2026)
Introduction: Numerous studies have revealed the importance of local support for successful restoration and conservation initiatives. Much less attention has been devoted to identifying the challenges and opportunities that influence community support. Objectives: To identify the challenges and opportunities influencing community engagement in coral reef restoration at Laughing Bird Caye National Park, Belize and its buffer zone. Methods: We interviewed restoration practitioners and key stakeholders, conducted a SWOT analysis with community members engaged in restoration efforts, and surveyed the broader public to evaluate local perceptions of the factors influencing community engagement in coral reef restoration. Results: Participant responses revealed four systems shaping local engagement: management, social, educational, and environmental. Key challenges included limited participation in restoration decisions, social dysfunction, low awareness of coral ecosystems, and environmental threats. Opportunities focused on expanding educational programs, particularly for youth, supporting local economies and livelihoods, promoting environmental stewardship, and strengthening governance through collaboration and local leadership. Conclusions: Our research revealed challenges that deter community engagement but also identified opportunities that may transform obstacles into actions to build trust, institutionalize collaborative participation, and empower local stewardship as a sustainable, community-driven process. Our results are specific to the community in Placencia, Belize but our methodology provides a potential roadmap for identifying stakeholder concerns and developing inclusive and effective programs to promote community engagement in restoration and conservation efforts elsewhere.